Pengaruh Konten Dakwah @mutiatreza dalam Media Sosial Instagram Terhadap Akhlak Mahasiswa Angkatan 2021 IAI AL-AZIS - Andani, Adisti Choiri; Abdurrazaq, Muhammad Nur Kholish; Tebba, Sudirman (Bahasa Indonesia, 2025)
Instagram has a significant role in spreading da'wah content to its followers. Acen, a little preacher, shares content that influences many people through Umma Acen's Instagram account. The content teaches Islamic values and good morals to the younger generation such as students. The purpose of this study is to determine the relationship between the attention of @mutiatreza's da'wah content on Instagram and the morals of the 2021 batch of IAI AL-AZIS students, as well as the effect of attention to @mutiatreza's da'wah content on Instagram on the morals of the 2021 batch of IAI AL-AZIS students. The quantitative approach applied in this study uses the S-O-R theory (Stimulus, Organism, Response) and media exposure theory in the attention dimension while frequency and duration are represented by responses in the form of likes. The correlation test is used to determine the relationship between the variables of da'wah content attention and student morals while simple linear regression is used to determine the effect of the independent variable on the dependent variable. The results showed that there is a significant positive relationship between the attention of @mutiatreza's da'wah content on Instagram and the morals of 2021 IAI AL-AZIS students, with a Pearson product moment correlation coefficient of 0.673 and a significance below 5%. Attention to @mutiatreza's preaching content on Instagram also has a positive effect on the morals of the 2021 batch of IAI AL-AZIS students, as indicated by the linear regression model, which can explain 45.3% of the variation in moral values influenced by attention to preaching content.